Spin pumping in ferromagnet-topological insulator-ferromagnetheterostructures - Baker, AA; Figueroa, AI; Collins-Mcintyre, LJ; van der Laan, G; Hesjedal, T (Nature Publishing Group, 2015)
Topological insulators (TIs) are enticing prospects for the future of spintronics due to their large spin-orbit coupling and dissipationless, counter-propagating conduction channels in the surface state. However, a means to interact with and exploit the topological surface state remains elusive. Here, we report a study of spin pumping at the TI-ferromagnet interface, investigating spin transfer dynamics in a spin-valve like structure using element specific time-resolved x-ray magnetic circular dichroism and ferromagnetic resonance. Gilbert damping increases approximately linearly with increasing TI thickness, indicating efficient behaviour as a spin sink. However, layer-resolved measurements suggest that a dynamic coupling is limited. These results shed new light on the spin dynamics of this novel material class and suggest great potential for TIs in spintronic devices, through their novel magnetodynamics that persist even up to room temperature.